Study on the discharge coefficients and the primary components of the pollutants from dismantling import waste electrical equipments - SHEN Dong-sheng; WANG Jun-qin; HE Yong-hua; CAI Bao-lin; LIANG Xiao-yong (浙江大学学报. 农业与生命科学版)
Through all-the-way tracking, investigation and in-situ analysis of the pollutants resulted from dismantling import waste electrical equipments, it was found that the primary components of the pollutants were total hydrocarbons, naphthalene and its derivatives, The discharge coefficient of naphthalene and its derivatives in the drainage was in the range of 0.156-0.186 mg/t, and the discharge coefficients of total hydrocarbons and naphthalene (including its derivatives) in the waste gas were 46.77-2066.6 mg/t and 9.0-398.7 mg/t, respectively.